ATRIBUSI KEKERASAN PADA PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Siti Rohmah Nurhayati (Jurnal Penelitian Humaniora, 2004)
Abstract This research aims to reveal the attribution of violence that was made by women victims of domestic violence. There were 45 women victims of domestic violence participate in this research. They were completed psychological scale of violence attribution. Data were analysis using descriptive statistic. The results of this research showed: (1) twenty three (51%) of subject were made tend external attribution for domestic violence were experience; (2) seventeen (37.8%) of subjects were made tend stable attribution domestic violence were experienced (3) twenty one (46.6%) of subject were made tend uncontrolled attribution domestic violence were experienced.